Renal infiltration presenting as acute kidney injury in Hodgkin lymphoma – A case report and review of the literature - Silva, Wellington Fernandes da (Leuk Res Rep, 2018)
Renal involvement in Hodgkin lymphoma (HL) is rare, although extralymphatic disease is usually found. Acute kidney injury is a recognized presentation of non-Hodgkin lymphoma, with bilateral kidney involvement, promptly requiring specific treatment. Regarding to HL, this manifestation is extremely rare and lacks pathologic description and management experiences. Herein, we describe a case of HL with atypical presentation as well as its management, current evaluation by PET-scan and histologic findings. This case report highlights clinical presentation and a successful experience on managing these cases. Moreover, it is important to drive biologic insights for understanding of kidney infiltration mechanism in HL.